Potassium Iodide/tert‐Butyl Hydroperoxide‐Mediated Oxidative Annulation for the Selective Synthesis of N‐Substituted 1, 2, 3‐Benzotriazine‐4(3H)‐ones Using Nitromethane as the Nitrogen Synthon. Issue 2 (5th January 2016) - Yan, Yizhe; Niu, Bin; Xu, Kun; Yu, Jianhua; Zhi, Huanhuan; Liu, Yanqi
Abstract: A novel and efficient oxidative annulation of 2‐aminobenzamides with nitromethane has been developed for the chemoselective synthesis of N ‐substituted 1, 2, 3‐benzotriazine‐4(3 H )‐ones in moderate to excellent yields under transition metal‐free conditions. Two NN bonds were constructed in one pot via CN cleavage of nitromethane, which was selectively employed as the nitrogen synthon. The preliminary mechanistic studies revealed that this protocol proceeded under hypoiodite catalysis generated in situ . Abstract :